The Yin and Yang of the Opioid Growth Regulatory System: Focus on Diabetes—The Lorenz E. Zimmerman Tribute Lecture - Joseph W. Sassani; Patricia J. Mc Laughlin; Ian S. Zagon (Journal of Diabetes Research)
The Opioid Growth Regulatory System consists of opioid growth factor (OGF), [Met5]-enkephalin, and its unique receptor (OGFr). OGF inhibits cell division when bound to OGFr. Conversely, blockade of the interaction of OGF and OGFr, using the potent, long-acting opioid receptor antagonist, naltrexone (NTX), results in increased DNA synthesis and cell division. The authors have demonstrated both in vitro and in vivo that the addition of exogenous OGF or an increase in available OGFr decreases corneal epithelial cell division and wound healing. Conversely, blockade of the OGF-OGFr interaction by NTX or a decrease in the production of the OGFr increases corneal epithelial cell division and facilitates corneal epithelial wound healing. The authors also have demonstrated that depressed corneal and cutaneous wound healing, dry eye, and abnormal corneal sensitivity in type 1 and type 2 diabetes in animals can be reversed by OGF-OGFr blockade by NTX. Thus, the function of the Opioid Growth Regulatory System appears to be disordered in diabetic animals, and its function can be restored with NTX treatment. These studies suggest a fundamental role for the Opioid Growth Regulatory System in the pathobiology of diabetic complications and a need for studies to elucidate this role further.